The Role of Edupreneurs in Islamic Boarding Schools - Hendri Hermawan ADINUGRAHA; Shovil MUNA; MUSTHOFA (Social Sciences and Education Research Review)
This study intends to describe the role of Edupreneur in Al-Ustmani Islamic Boarding School. The method used in this study uses a qualitative approach. In this study, researchers used exploratory and descriptive research forms. The setting of this research is the Al-Ustmani Islamic Boarding School. The sampling technique used was purposive sampling technique, namely the technique of determining sampling with certain considerations, based on considerations that the samples in this study were students, teachers, and the Al-Ustmani Islamic Boarding School foundation. The technique used for data collection and validity is source triangulation. The findings of this study state that edupreneurs at the Al-Ustmani Islamic Boarding School play an important role in the progress of the current world of education. Entrepreneurship or edupreneur education, such as that carried out by the Al-Ustmani Islamic Boarding School Foundation, is naturally required for all Islamic religious education institutions, so it is no longer only recommended as it is today. In the Edupreneurship of the Al-Ustmani Islamic Boarding School, the students must be invited to the field to see business objects directly. Before graduating, the students of the Al-Ustmani Islamic Boarding School must be required to practice entrepreneurship with capital from the institution, which capital must be returned after the students graduate from the Al-Uthmani Islamic Boarding School without interest. Entrepreneurship learning at the Al-Ustmani Islamic Boarding School is not all theoretical, but there is practice in laboratories and workshops to produce products, so that students and graduates have experience in producing products that can open up business opportunities. The Edupreneurship curriculum at Al-Ustmani Islamic Boarding School is designed to produce graduates who are able to think creatively in order to produce innovators who are able to create change and progress for the Indonesian nation.